Economic growth in OPEC nations: The role of renewable energy consumption, CO2 emissions, and foreign direct investment - Camila, Elmira Mufliha; Agustin, Grisvia; Sumarsono, Hadi (Social, Ecology, Economy for Sustainable Development Goals Journal, 2024)
Background: The nations that make up OPEC (the Organization of the Petroleum Exporting Countries) have traditionally depended on gas and oil export earnings. However, there is a significant global shift towards renewable energy in an effort to reduce the impact of climate change. This research aims to analyze the effect of Renewable Energy Consumption, CO2 Emissions, and Foreign Direct Investment (FDI) on the Economic Growth in OPEC Nations partially and simultaneously. Methods: In this research, panel data regression analysis techniques are combined with quantitative research approaches. Secondary data from the World Development Indicators (WDI) for the years 2001–2020 were used in this research. Finding: This research showed that the Renewable Energy Consumption and CO2 Emissions variables do not affect economic growth in OPEC countries. Meanwhile, the foreign direct investment variable has a positive and significant effect on economic growth in OPEC countries. Conclusion: OPEC countries need to diversify their economies and CO2 reduce their dependence on oil as there is a global shift towards cleaner energy. Novelty/Originality of this article:  This study analyzes the impact of Renewable Energy Consumption, CO2 Emissions, and Foreign Direct Investment on Economic Growth in OPEC countries using panel data regression analysis. The study's findings show that only Foreign Direct Investment positively and significantly impacts economic growth.